(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the linguistic features, artistic aspects and views of the social poetry of Muhammadsiddiq Hayrat. The author tried to analyze the language, style, artistic features and poetic skills of Hayrat Bukhari’s works, as well as the literary environment of the Bukhara Emirate. In particular, special attention is given to the use of artin the poems of Muhammad Siddiq Hayrat, their linguistic and stylistic features, and other unexplored issues related to the poet’s life and work. This determines the value of the poet’s poems, which have not yet been sufficiently researched, and their place in the history of Tajik literature of the late ХIХth and early ХХth centuries.